2021
DOI: 10.3390/vaccines9050502
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Severity of Post-Vaccination Reactions after Vaccination against COVID-19

Abstract: The pandemic of COVID-19 might be limited by vaccination. Society should be vaccinated to prevent the spread of coronavirus disease 2019 (COVID-19) and to protect persons who are at high risk for complications. In Poland, the National Vaccination Program has been introduced, which is a strategy for planning activities to ensure safe and effective vaccinations among Polish citizens. It includes not only the purchase of an appropriate number of vaccines, their distribution but also monitoring of the course and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
1
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 23 publications
9
53
1
11
Order By: Relevance
“…These cutaneous reactions close to the injection site are common just as in other vaccines, 5 and our result concurs well with a study conducted in Jordanian and Polish health workers. 20 , 23 But this finding is higher than another prospective observational study conducted in the United Kingdom, which has shown injection site symptoms among 58.7% of study participants. 19 Among the reported injection site symptoms, the commonest being injection site pain (65.48%) followed by tenderness (57.89%).…”
Section: Discussionmentioning
confidence: 65%
“…These cutaneous reactions close to the injection site are common just as in other vaccines, 5 and our result concurs well with a study conducted in Jordanian and Polish health workers. 20 , 23 But this finding is higher than another prospective observational study conducted in the United Kingdom, which has shown injection site symptoms among 58.7% of study participants. 19 Among the reported injection site symptoms, the commonest being injection site pain (65.48%) followed by tenderness (57.89%).…”
Section: Discussionmentioning
confidence: 65%
“…To date, several independent (non-sponsored) phase IV studies on mRNA-based COVID-19 vaccines have been published from various countries, e.g., Czech Republic, Germany, Greece, Iraq, Italy, Jordan, Malta, Poland, Saudi Arabia, the UK, and the USA [13,[19][20][21][22][23][24][25][26][27][28][29][30]. The results of these phase IV studies generally agreed with the results of the phase III trials executed by the manufacturers and published by the regulators, i.e., the Centers for Disease Control and Prevention (CDC) [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…These hybrid systems are needed now more than ever because they can overcome the drawbacks of sole passive surveillance and active surveillance systems. Jęśkowiak et al (2021) evaluated the Polish passive surveillance system and concluded that it was unreliable in the case of COVID-19 vaccines vigilance, as they compared its data to targeted active studies and found serious discrepancies [13].…”
Section: Introductionmentioning
confidence: 99%
“…One-quarter of the participants (25.5%) reported that their vaccination decision would be influenced by the vaccine side effects being monitored closely by competent authorities. A recent Polish study demonstrated that passive surveillance systems used widely by the governments to monitor COVID-19 vaccine side effects were ineffective, thus bolding the demand for active surveillance of COVID-19 vaccine side effects by independent (non-sponsored) studies [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. The students who reported to need this evidence the most are mainly females, non-HCS, influenced by media and social media, mistrusting their healthcare providers and pharmaceutical industry, and with immunity misconception and insufficient perceived knowledge.…”
Section: Discussionmentioning
confidence: 99%